Neighbourhood Regeneration in Istanbul: from Earthquake Mitigation to Planned Displacement and Gentrification - Gökşin, Zeynep Ayşe; Gibson, Mike (My University, 2016)
The paper analyses the development of neighbourhood regeneration in Istanbul since the 1999 marmara earthquake, contrasting initial concepts and policy recommendations with actual policies and outcomes. An historical analysis of Turkish urbanisation identifies the specific characteristics which have influenced a shift from the concept of neighbourhood regeneration as earthquake mitigation to private sector-led redevelopment which fails to target earthquake vulnerable neighbourhoods but delivers planned gentrification. The analysis identifies three phases in the recent emergence of neighbourhood regeneration in Istanbul. The first was a series of studies and pilot projects which established the key components of a Turkish model of earthquake resilient redevelopment of poor neighbourhoods, with minimum gentrification. The second was dominated by the implementation of pioneering projects with controversial gentrification outcomes. The 2012 Urban Regeneration law has established the parameters of the third phase dominated by the launch of a national programme. This evolutionary process is illustrated by a case study of Bağcılar. The paper concludes that the challenges of neighbourhood regeneration are rooted in Turkey specific historical urbanisation processes. Current neo-liberal redevelopment policies will not protect the urban poor from future earthquakes but this situation may change as the earthquake threat regains the attention of policy makers
Keywords: neighbourhood regeneration; earthquake resilience; Istanbul